Pathogenicity, transmissibility, and fitness of SARS-CoV-2 Omicron in Syrian hamsters - Yuan, Shuofeng; Ye, Zi-Wei; Liang, Ronghui; Tang, Kaiming; Zhang, Anna Jinxia; Lu, Gang; Ong, Chon Phin; Man Poon, Vincent Kwok; Chan, Chris Chung-Sing; Mok, Bobo Wing-Yee; Qin, Zhenzhi; Xie, Yubin; et al. (Science (American Association for the Advancement of Science), 2022)
The in vivo pathogenicity, transmissibility, and fitness of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron (B.1.1.529) variant are not well understood. We compared these virological attributes of this new variant of concern (VOC) with those of the Delta (B.1.617.2) variant in a Syrian hamster model of COVID-19. Omicron-infected hamsters lost significantly less body weight and exhibited reduced clinical scores, respiratory tract viral burdens, cytokine and chemokine dysregulation, and lung damage than Delta-infected hamsters. Both variants were highly transmissible through contact transmission. In noncontact transmission studies Omicron demonstrated similar or higher transmissibility than Delta. Delta outcompeted Omicron without selection pressure, but this scenario changed once immune selection pressure with neutralizing antibodies—active against Delta but poorly active against Omicron—was introduced. Next-generation vaccines and antivirals effective against this new VOC are therefore urgently needed. There is growing evidence that the Omicron variant of concern (VOC) is more transmissible and infectious than previous iterations of severe acute respiratory syndrome coronavirus 2. Yuan et al . compared Syrian hamsters exposed to either Omicron or Delta VOCs. Animals infected with Omicron showed lower respiratory tract viral burdens and reduced clinical severity. Nevertheless, Omicron was at least as transmissible as Delta, if not more so. When animals were challenged with a mixture of both variants, Delta outcompeted Omicron in naïve hamsters. This competitive advantage disappeared, however, in vaccinated animals. Moreover, vaccinated hamsters were better than unvaccinated animals at transmitting Omicron to co-housed companions. This work helps to clarify how Omicron might have gone on to become the predominant strain in populations with high rates of previous infection and vaccination. —STS Less pathogenic but highly transmissible, SARS-CoV-2 Omicron can outcompete Delta under immune selection pressure.